Corporate social responsibility, sustainable business environmental, social and governance frameworks for the 21st century - Lindsay, Rae, LL. M.; Martella, Roger Romulus (International Bar Association series ;, 2020)
"[This book] explores the evolving field of corporate social responsibility (CSR). In a dramatic departure from its voluntary origins, CSR is rapidly shifting to hold multinational companies accountable for more than traditional shareholder performance. This CSR movement is embracing new environmental, social and governance (ESG) frameworks that promote global sustainability goals and enhance accountability for negative impacts businesses can have on 'planet and people'. It also focuses on the positive role corporations play in supporting the international community's efforts to achieve the UN Sustainability Goals by 2030. The collection of chapters by leading businesspeople, international civil servants, legal practitioners, academics and other experts offers a forward-looking and pragmatic perspective that illuminates the major themes in this movement towards increasingly sustainable, transparent and accountable business practices" --